Pengaruh Kepercayaan dan Kualitas Pelayanan terhadap Kepuasan Nasabah: Studi Kasus pada KSU Br. Gelumpang, Sukawati di Gianyar - Bayu, I Gede Risky Indra; Wijaya, Putu Yudy; Wulandari, Ni Luh Adisti Abiyoga (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Customer satisfaction is a person's feeling of pleasure or disappointment that comes from a comparison between his impression of a product's performance or results and other expectations. To achieve customer satisfaction, it is necessary to have good service quality and a high level of trust. This study aims to determine the effect of trust and service quality on customer satisfaction. The research was conducted at KSU Banjar Gelumpang, Sukawati, Gianyar which is located at Banjar Gelumpang, Sukawati, Gianyar. The number of samples used in this study amounted to 100 respondents who were KSU Banjar Gelumpang customers who were taken using a proportional random sampling method. Validity and reliability tests were used to test research instruments. The analysis technique used is the classical assumption test, multiple linear regression analysis, determination analysis, t-test, and F test. Based on the research results, it can be seen that service quality has a positive and significant partial effect on customer satisfaction at KSU Br. Gelumpang, trust has a positive and partially significant effect on customer satisfaction at KSU Br. Gelumpang and service quality and trust have a positive and significant effect simultaneously on customer satisfaction at KSU Br. Gelumpang.